Korelasi indeks massa tubuh terhadap rasio trigliserida dan high-density lipoprotein-cholesterol pada wanita usia subur dengan obesitas - Nina Indriyani Nasruddin; Juminten Saimin; Ramadhan Tosepu (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2022)
Body mass index correlation with triglyceride and high-density lipoprotein-cholesterol ratio of reproductive age women with obesityBackground: Obesity in women of reproductive age is thought to be one of the triggers of coronary heart disease. Body mass index (BMI) correlates well with the percentage of body fat, which is a strong indicator of coronary heart disease. Accumulation of visceral adipocytes releases excess free fatty acids, resulting in increased triglyceride synthesis. Furthermore, in a state of hypertriglyceridemia, there is a decrease in HDL levels and an increase in HDL catabolism resulting in decreased HDL levels. Examination of the ratio of triglyceride levels and high-density lipoprotein cholesterol (TG/HDL-C) is a strong indicator of cardiovascular disease.Objective: The aim of his study was to investigate the correlation between BMI and TG/HDL-C ratio in women of reproductive age.Methods: Using an analytical approach with a cross-sectional design. Furthermore, height and weight were measured with Smic ZT 120. At the same time as this examination, venous blood was taken from the median cubital area to be used to check the level of triglycerides and HDL-C in the serum. TG examination with GPO-PAP and HDL-C direct method. The bivariate analysis uses the Spearman Rank correlation test, while the multivariate analysis uses the linear regression test.Results: TG levels were 106 (34-363) mg/dl, HDL-C levels were 48.19 ± 9.91 mg/dl, and the ratio between the two was 2.26 (0.52-9.58). Spearman Rank analysis obtained the value of r was 0.573, p-value 0.0001.Conclusions: There is a significant positive correlation between BMI and the ratio of TG/HDL-C levels in adult women of reproductive age with obesity.